Treatment of corn with lactic acid delayed in vitro ruminal degradation without compromising fermentation: a biological and morphological monitoring study - Tian, K. E.; Luo, Gan; Aldian, Dicky; Yayota, Masato (Frontiers in Veterinary Science, 2024)
Grain processed by lactic acid (LA) is known to improve ruminant growth and health. However, the exact mechanism regarding rumen hydrolysis of LA-treated grain is still ambiguous. This experiment was designed to compare the effects of 5% LA treatment on the trophic and morphological variations in corn and to discover the alternations in ruminal hydrolysis between LA-treated and untreated corn macroscopically and microscopically using in vitro fermentation method. The results showed that, compared with untreated corn (CN), corn treated with 5% LA for 48 h (CNLA) experienced a decrease in the dry matter, albumin fraction, aNDFom, and water-soluble carbohydrate content but an increase in the resistant starch content. The in vitro fermentation showed that the pH of CNLA was higher, but dry matter disappearance was lower than that of CN. Most of the fermentation indices were unaffected, except for decreased iso-butyrate and iso-valerate. The abundances of total bacteria, Prevotella spp., Streptococcus bovis, and Selenomonas ruminantium were higher, but those of Ruminococcus flavefaciens and Ruminococcus albus were lower in CNLA than in CN. There were differences in the scanning electron micrographs between CNLA and CN after 3 h of fermentation. This study suggests that treating corn with LA for 48 h can induce changes in its nutrient composition and alter the bacterial flora during subsequent in vitro fermentation. These changes appeared to be crucial contributors to the beneficial effects observed in rumen fermentation.